Amyloid Nanofibril-Assisted Spray Drying of Crumpled Supraparticles - Kämäräinen, Tero; Nakayama, Yuzuki; Uchiyama, Hiromasa; Tozuka, Yuichi; Kadota, Kazunori (Small, 2024)
Nanofibrils are known to improve the cohesion of supraparticle (SP) assemblies. However, tailoring the morphology of SPs using nanofibrillar additives is not well developed. Herein, β-lactoglobulin amyloid nanofibrils (ANFs) are investigated as means to impart morphological control over the assembly process of spray-dried SPs composed of 10–100 nm silica nanoparticles (SiNPs). Phytoglycogen (PG) and silver nanowires (AgNWs) are used to assess the influence of building block softness and aspect ratio, respectively. The results demonstrate that ANFs promote the onset of structural arrest during the particle consolidation enabling the preparation of corrugated SP morphologies. The critical ANF loading required to induce SP corrugation increases by roughly 1 vol% for every 10-nm increase in SiNP diameter, while the ensuing ANF network density decreases with SiNP volume fraction and increases with SiNP diameter. Results imply that ANF length starts to become influential when it approaches the SiNP diameter. ANFs display a reduced effectiveness in altering soft PG SP morphology compared with hard SiNPs of comparable size. In SiNP–AgNW SPs, ANFs induce a toroid-to-corrugated morphology transformation for sufficiently large SPs and small SiNPs. The results illustrate that ANFs are effective additives for the morphological engineering of spray-dried SPs important for numerous applications.
Created from Fastlane, Scopus look-up
Keywords: amyloid nanofibrils; crumpling; glycogen; silver nanowires; spray drying; supraparticles